OH reactivity at a rural site (Wangdu) in the North China Plain: contributions from OH reactants and experimental OH budget - Fuchs, Hendrik; Zhaofeng Tan; Lu, Keding; Bohn, Birger; Broch, Sebastian; Steve S. Brown; HuaBin Dong; Sebastian Gomm; Rolf Häseler; He, Lingyan; Hofzumahaus, Andreas; Holland, Frank; et al. (Atmospheric Chemistry and Physics, 2017)
In 2014, a large, comprehensive field campaign was conducted in the densely populated North China Plain. The measurement site was located in a botanic garden close to the small town Wangdu, without major industry but influenced by regional transportation of air pollution. The loss rate coefficient of atmospheric hydroxyl radicals (OH) was quantified by direct measurements of the OH reactivity. Values ranged between 10 and 20 s(-1) for most of the daytime. Highest values were reached in the late night with maximum values of around 40 s(-1). OH reactants mainly originated from anthropogenic activities as indicated (1) by a good correlation between measured OH reactivity and carbon monoxide (linear correlation coefficient R-2 = 0 : 33) and (2) by a high contribution of nitrogen oxide species to the OH reactivity (up to 30% in the morning). Total OH reactivity was measured by a laser flash photolysis-laser-induced fluorescence instrument (LP-LIF). Measured values can be explained well by measured trace gas concentrations including organic compounds, oxygenated organic compounds, CO and nitrogen oxides. Significant, unexplained OH reactivity was only observed during nights, when biomass burning of agricultural waste occurred on surrounding fields. OH reactivity measurements also allow investigating the chemical OH budget. During this campaign, the OH destruction rate calculated from measured OH reactivity and measured OH concentration was balanced by the sum of OH production from ozone and nitrous acid photolysis and OH regeneration from hydroperoxy radicals within the uncertainty of measurements. However, a tendency for higher OH destruction compared to OH production at lower concentrations of nitric oxide is also observed, consistent with previous findings in field campaigns in China.